Analisis Makna Semantik Dalam Puisi “Aku” Karya Chairil Anwar - Agus Sibagariang; Anggi Rahmawati; Rindy Any Br Tarigan; Vika Maria Sagala; Yuliana Sari (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research introduces an analysis of semantic meaning in the poem "Aku" by Chairil Anwar. Using a qualitative approach, this research explores the lexical and grammatical meaning of each word and phrase in the poem. By referring to the concepts of lexical and grammatical semantics, this research describes how the words in poetry contain deep and varied meanings, implicitly expressing the poet's feelings and thoughts. The results of the analysis show that each word in the poem makes a rich contribution to the overall interpretation of this literary work. This research aims to provide in-depth insight into Chairil Anwar's poetic expressions and the importance of understanding semantic meaning in a literary context.